Lebanon: Legal and Judicial Sector Assessment - (:unkn) unknown (My University, 2016)
Legal and judicial reform constitutes one of the main pillars of the World Bank’s Comprehensive Development Framework (CDF) to promote economic growth and alleviate poverty. Since the end of the civil war over ten years ago, Lebanon has slowly started the process of rebuilding its government and public institutions. The legal and judicial sector is still, however, suffering from the lingering effects of the civil war. Though Lebanon has a long standing history of prominence in this field, much of the sector was demolished by the war. The institutions and actors in this sector are now starting to undertake reforms to regain their prominence. The issues that plague this system are similar to those of many countries - the courts are backlogged from a shortage of judges and court staff, the rule of law has not prevailed, and there are concerns about the judiciary’s independence in the political system in place.